The Urgency of Recognizing the 'Opt-Out Right' to Protect Consumer Personal Data in P2P Lending Fintech - Nadia Carolina Weley; Shenti Agustini; David Tan; Tony Wibowo; Tony Tan (Greenation Research & Yayasan Global Resarch National, 2026)
Financial Technology (FinTech) has significantly advanced financial services in the digital era, with Peer-to-Peer (P2P) lending platforms emerging as a major example. While these platforms provide financial assistance, many operate under the principle of